Over a million students use our free study notes to help them with their homework
Step 1: Differentiate y with respect to x. dy/dx = 3x^2 - 6x - 9Step 2: Equate to zero and solve. 3x^2 - 6x - 9 = 0(x - 3)(x+1) = 0x = 3, x = -1Step 3: Substitute into original equation to fin...
First, I would label the two equations 1 and 2:(1) 3x+by=5(2)x-y=-2Next, multiply (2) by 3 and subtract this equation from (1) in order to cancel out the x terms: 3x+by=5-(3x-3y=-6)This results in the equ...
Th equation of a line is denoted as y = mx + c, with m as the slope and c as the y intercept. We already know that the slope is 2. Since the line passes through the point (7, 5)...
24x^2+8x
We know that (8/27)^(1/3). = (2/3)Then do (2/3)^2 = (4/9)Split up 2/3, into powers of 1/3, and 2.
←
600
601
602
603
604
→
Internet Safety
Payment Security
Cyber
Essentials